PENTINGNYA PENGEMBANGAN ZONA SELAMAT SEKOLAH DEMI KESELAMATAN BERSAMA DI JALAN RAYA (Suatu Tinjauan Pustaka) - Suweda, I Wayan (Jurnal Ilmiah Teknik Sipil; Vol. 13, No. 1 Januari 2009)
The development of transport technology and human’s culture, which usually require all thing must goes fastly, often makes human being especially children as victims including traffic accident victims. In terms of road safety in the surrounding school, students hopefully come and leave their school safely by developing Safe School’s Zone (SSZo). SSZo is a zone on a link-road at the surroundings of school which traffic speed is based on certain time. By traffic management and traffic engineering, the safe school zone is equipped with supporting building and complement facility to control strictly the speed of through traffic. For this reason, in the safe school zone, the traffic hopefully will be safe, comfort, easy to be found and economic. In this study, it will be discussed the importance of SSZo, the types of SSZo, supporting building and complement facility needed and also some actions that should be carried out to make its management successfull.
Keywords: Safe School’s Zone, Traffic Management, Traffic Engineering.